(untitled) (Research, Society and Development, 2020)
In addition to the traditional activities of handling, stock control and distribution of parenteral nutrition formulations, in recent years, studies have shown that the pharmacist’s collaboration in the patient care process is strategic. In this sense, this study aimed to discuss, through an integrative review of the literature scientific, the possibilities for the contribution of pharmaceutical care to patients using parenteral nutrition. Articles published between 2015 and 2020, written in english, spanish or portuguese, were recruited in the Virtual Health Library, Pubmed and Scielo databases. The literature addresses as contributions of pharmaceutical care to this group of patients: the improvement of nutritional support; assessing the functionality and safety of parenteral nutrition, by monitoring laboratory tests and other indicators; the prevention and treatment of mechanical, infectious and metabolic complications; investigation and intervention in cases of drug-parenteral nutrition interactions and between formula components; investigation, intervention and notification of adverse events; health education for professionals, caregivers, family members and patients; support for the work processes of the nutritional support team; the development of shared consultations in a multidisciplinary context and the development and validation of protocols for assistance support.